Factors associated with physical activity level among adolescents in Sarawak, Malaysia - Law, Leh Shii; Mohd Taib, Mohd Nasir; Abu Saad, Hazizi (Sports Science Unit, School of Medical Science, Universiti Sains Malaysia, 2014)
Physical inactivity among adolescents has been reported to be on an uprising trend and has been gaining attention among public health practitioners and policy makers. This cross-sectional study was conducted to investigate associations between sociodemographic, psychological, physical environmental characteristics, and body weight status with physical activity level among adolescents at four randomly selected national multi-racial secondary schools in Sibu, Sarawak. Data collection was carried out by using a self-administered questionnaire whereas weight and height of the students were measured using standard procedures. A total of 375 students were recruited (male: 32.0%, female: 68.0%). Overall, physical activity level among the adolescents was low, with 65.9% of the students categorized in the low category, 31.7% in moderate, and only 2.4% in the high category. In bivariate analysis, sex, ethnicity, eating attitudes, physical activity self- efficacy, neighborhood recreation facilities, land-use mixed-access, street connectivity, walking/cycling facilities, and neighborhood aesthetics were significantly associated with physical activity level. In multiple linear regression, physical activity self efficacy, sex, ethnicity, neighborhood aesthetics, land-use mixed access, and eating attitudes were found to contribute to 31.2% of the variance in physical activity level of the adolescents. Any future intervention programs to promote physical activity among adolescents in Malaysia should consider incorporating the factors identified in the present study into its planning to increase their effectiveness.